Pengaruh Penggunaan CDI Standar Dan CDI Digital Terhadap Daya Dan Torsi Motor Bensin 250CC - Muhamad Nur Safi’i; Faris Naufal Hanif; Naufal Dwi Qurniawan; Adzandani Muhammad; Trisma Jaya Saputra (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study was to determine the difference in power, torque and fuel consumption produced by a 250 cc CRF motorbike using standard CDI ignition and digital CDI with Pertamax fuel. The research method used was an experiment conducted on a 250 cc CRF motorbike. The research data were analyzed by directly observing the experimental results and then concluding and determining the results of the research that had been carried out in the form of graphs and tables. In testing the combustion engine, a chassis dynamometer is used to determine the power and torque produced, while to measure the level of fuel consumption using a graphimetric method, namely by weighing the consumption of fuel consumed during a certain time interval. The results of the study show that there is an influence on the performance of the combustion engine, power, torque, and fuel consumption produced in an internal combustion engine with standard CDI ignition variations and using a digital CDI for Pertamax fuel. Maximum motor fuel power produced by standard CDI ignition of 5.6 hp at 9000 rpm engine speed. The maximum engine combustion torque generated from the racing CDI ignition is 5.9 Nm at 6000 rpm engine speed. While the lowest fuel consumption when using digital CDI is 0.281 kg/hour. In conclusion, the greatest power is obtained when using a standard CDI, the greatest torque is obtained when using a digital CDI and the lowest fuel consumption can be obtained by using the right ignition, in this case using a racing ignition CDI.